A Postsynaptic Role for Short-Term Neuronal Facilitation in Dendritic Spines - Yang, Sunggu; Santos, Mariton D.; Tang, Cha-Min; Kim, Jae Geun; Yang, Sungchil (Frontiers in Cellular Neuroscience, 2016)
Synaptic plasticity is a fundamental component of information processing in the brain. Presynaptic facilitation in response to repetitive stimuli, often referred to as paired-pulse facilitation (PPF), is a dominant form of short-term synaptic plasticity. Recently, an additional cellular mechanism for short-term facilitation (short-term postsynaptic plasticity) has been proposed. While a dendritic mechanism was described in hippocampus, its expression has not yet been demonstrated at the levels of the spine. Furthermore, it is unknown whether the mechanism can be expressed in other brain regions, such as sensory cortex. Here, we demonstrated that a postsynaptic response can be facilitated by prior spine excitation in both hippocampal and cortical neurons, using 3D digital holography and two-photon calcium imaging. The coordinated action of pre- and post-synaptic plasticity may provide a more thorough account of information processing in the brain.